Anos potenciais de vida perdidos por homicídio na Bahia, segundo a raça/cor da pele, 2001-2016: aspectos epidemiológicos e temporais - Jesus, Samuel José Amaral (2019)
Among the violent deaths, homicides are the main cause of death in the country, due to the rapid growth of the population and the victimization of young people, the main victims. This picture leads to a greater loss of potential years of life, which accounts for the number of years not lived because of an early death. This situation is aggravated when analyzing the differences in race and color of the skin, which determine the lack of equity between racial segments. The state of Bahia gains evidence of high homicide rates, as it contains many of the cities that exhibit the highest levels of crime. This study analyzed homicide mortality in the cities of Feira de Santana and Salvador, between 2001 and 2006, according to race/color of the skin. For this purpose, the Potential Years of Life Lost (PYLL) indicator and the temporal trend analysis of the PYLL rates for the cities of the study were used, using the linear regression model with correction proposed by Prais-Winstein (PW). As databases, the Mortality Information System (MIS) and the Brazilian Institute of Geography and Statistics (BIGS) were used. The statistical analysis contemplated the descriptive measures with emphasis on the indicator and the temporal analysis was performed according to the variation of the rates. In total, there were 22,818 homicide deaths, equivalent to a loss of 940,288 potential years of life, and a rate of 2,664.1 years per 100,000 inhabitants. Young black males were the main victims, as they lost 23.3 times more years of life than whites. Many of those deaths occurred on the public highway, and the firearm was the main instrument for aggression. We found an increasing tendency in the variables (β1> 0) and there was autocorrelation of the errors when the Durbin-Watson test (D-W) was executed, which justifies the Prais-Winsten method. The rates of PYLL were 10.0% (β1> 0 and p-value <0.05) for Feira de Santana, and 6.4% (β1> 0 and p-value <0, 05) to Salvador. It is expected that, with this study, there will be an update regarding the homicide mortality scenario in the State of Bahia, which will contribute to the reflection on the subject, to overcome social inequities in health and to stimulate prevention, in order to generate changes in the panorama of mortality of young people in the country